The efficacy of oral ephedrine in prevention of hypotension following spinal anesthesia in LSCS (Health Renaissance, 2015)
Background: Systemic hypotension is seen frequently after spinal anesthesia   in obstetric population and if untreated can lead to maternal and fetal complications.   Ephedrine, via various routes, has been used both as prophylaxis and treatment of this hypotension. Oral ephedrine has been found to be effective in prevention of   hypotension in non obstetric patients after neural block. Objective: To study the   efficacy of oral ephedrine in prevention of hypotension following spinal anesthesia in   LSCS and to assess the neonatal outcome. Methods: It was a randomized, controlled   double blinded study involving 100 parturients undergoing LSCS. Total duration   of study was two years. A preformed structured proforma was used to record the   data incidence of hypotension and neonatatal APGAR score were the main outcome   variables. This study was carried out in 100 ASA physical status I and II patients   admitted for emergency and elective LSCS. Fifty patients received placebo and 50   patients received prophylactic ephedrine orally, before spinal anesthesia. The two   groups were compared in respect of their incidences of hypotension and maintenance   of SBP and neonatal outcome. Results: The incidence of hypotension was much higher in patients who received placebo than who received prophylactic ephedrine orally (19 vs. 6). APGAR score for assessment of neonatal wellbeing was similar   in two groups. Conclusions: The prophylactic oral ephedrine 30 mg, given 30-45 minutes before LSCS, is a simple and effective measure to prevent hypotension   following spinal anesthesia and it does not have any adverse effect on neonatal  outcome.   Health Renaissance 2014;12(2): pp: 118-123